Open defecation can be condensed only by improving female literacy rate. - JANA, SUBRATA; MISHRA, ABHIJIT; KALI, SUKHEN (IJRDO - Journal of Social Science and Humanities Research, 2017)
Indian rates of open defecation are uniquely high, much higher than in many poorer countries. This note asks why rural India has uniquely high rates of open defecation. Although the evidence is overwhelmingly clear that the reduction of open defecation in rural India will not be importantly accelerated by the large investments in government latrines proposed by the  ‘Swachh Bharat Mission’, it is not a suitable way to accelerating the reduction of open defecation in rural India. We know, mother is the best teacher to their children. An educated womanhasability to solve family problems & learn new skills to play a role in country economy. Only woman is the lastresort, that she can change our environment. So, thanks to different creativities by the state Government as well as the central Government. The strategies introduced by the Indian Government have upgraded the education status of women but still lot of work needs to be done. “Women education reflects country development”. Every family takes a vital step to educate & save the girl child. So, Indian government takes ‘BetiBanchaoBetiPadhao’ programme. In conclusion, it is says that women education is only way to solve this social disease. Open defecation also harmful for our child. Major part of malnutrition is coming from infectivity of open defecation.